The consumer society and the postmodern city - Clarke, David B., 1964- (Routledge, 2003)
Working through the often controversial ideas of the consumer society's most influential theorists, Jean Baudrillard and Zygmunt Bauman, this book assesses the ways in which consumerism is reshaping the nature and meaning of the city.